2012
DOI: 10.1093/icb/ics064
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Developmental Mode and Its Effect on Population Genetic Structure of a Spionid Polychaete, Pygospio elegans

Abstract: Population genetic structure of sedentary marine species is expected to be shaped mainly by the dispersal ability of their larvae. Long-lived planktonic larvae can connect populations through migration and gene flow, whereas species with nondispersive benthic or direct-developing larvae are expected to have genetically differentiated populations. Poecilogonous species producing different larval types are ideal when studying the effect of developmental mode on population genetic structure and connectivity. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 72 publications
2
46
0
Order By: Relevance
“…For example, even in the exposed sand flat population in UK, local currents may facilitate larval retention [40]. Continuous high local larval retention could lead to the spatial genetic structure pattern seen in P. elegans (shown here and in [42]), as well as to the high F IS values observed in these populations. Recent studies have shown that local larval recruitment in the marine habitat may be more common than assumed [4,85,86].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, even in the exposed sand flat population in UK, local currents may facilitate larval retention [40]. Continuous high local larval retention could lead to the spatial genetic structure pattern seen in P. elegans (shown here and in [42]), as well as to the high F IS values observed in these populations. Recent studies have shown that local larval recruitment in the marine habitat may be more common than assumed [4,85,86].…”
Section: Discussionmentioning
confidence: 88%
“…In some populations multiple larval types have been observed simultaneously or seasonally [35,36,42], but many populations of P. elegans are known to produce only one larval type (e.g. [34,40,46]).…”
Section: Introductionmentioning
confidence: 99%
“…P. elegans has been described as opportunistic and it can be found in many different habitats with different salinities and temperatures, but it thrives in sandy intertidal mud flats (Anger, 1984;Kesäniemi, Geuverink, & Knott, 2012;Morgan, 1997). P. elegans has been described as opportunistic and it can be found in many different habitats with different salinities and temperatures, but it thrives in sandy intertidal mud flats (Anger, 1984;Kesäniemi, Geuverink, & Knott, 2012;Morgan, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…P. elegans exhibits polymorphism in its reproductive and developmental strategies (Kesäniemi et al, 2012;Rasmussen, 1953Rasmussen, , 1973). Females can produce either a small number of benthic larvae that are brooded in the egg capsules throughout their development (these larvae lack a dispersive, freeswimming stage), or females can produce a large number of planktonic larvae that are only briefly brooded before they emerge from the egg capsules to complete their development in the plankton (see details in Kesäniemi et al, 2012;Thonig, Banta, Winding Hansen, & Knott, 2016). After internal fertilization, females lay embryos into egg capsules inside the maternal tube where the larvae are brooded.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes within a single family (such as Nereididae), there are species that have all stages of development from trochophore to an adult segmented worm ( Platynereis dumerilii ), as well as species with direct development ( Neanthes arenaceodentata ) [10,13,14]. Finally, different individuals of the same species can have direct development as well as development through a larval stage; moreover, the larvae can be of different types (planktonic and benthic) [15,16]. …”
Section: Introductionmentioning
confidence: 99%